Phylogenetic Relationships of Locally Cultivated Garcinia Species with Some Wild Relatives - Saleh, Mohd Nazre; Mansor Clyde, Mahani; Mohamad, Abdul Latiff (2007)
Garcinia is known for their edible fruit and a number of species from the wild have been selected and cultivated not just for their fruits but also for other uses such as vegetables and traditional medicine. Phylogenetic relationships of five locally cultivated and 12 wild species of Garcinia were determined using the sequence of the internal transcribed spacer region (ITS). Sequence analysis generated by both Parsimony and Bayesian inference resulted in almost identical tree topology containing five main monophyletic clades. The monophyly of these clades are congruent with previous taxonomic classification although a few clades require more representative samples to give clearer picture. Garcinia cowa (kandis) and G. atroviridis (asam gelugor) clustered within sect. Brindonia, G. hombroniana (beruas) and G. mangostana (mangosteen) fall within clade of sect. Garcinia and G. prainiana (kecupu) exhibit as basal clade of sect. Xanthochymus.